Exercise For Rehabilitation After ACL Recontruction To Improve Neuromuscular & Strenght And Return To Sport - Nia Hayati; Umi Budi Rahayu; Halim Mardianto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction: The incidence of anterior cruciate ligament (ACL) rupture is estimated to range from 30 to 78 per 100,000 people/year. After ACL reconstruction, 61% to 89% of athletes successfully return to sport, usually at 8 to 18 months after reconstruction, depending on the level of play. Surgical reconstruction of the ACL is often indicated to restore functional stability during athletic activity and prevent early degeneration of the knee. Case Presentation: A 17-year-old male patient with a diagnosis of post ACL reconstruction, and has entered phase 2 complained of knee pain when performing full flexion movements, especially when performing prostrate prayer movements and sitting tahiyat akhir. Management and Results: Patients attended 6 therapies, 1 therapy for 180 minutes for 2 weeks, with a therapy program in the form of SEBT (Star Exvursion Balance Test) exercises, dynamic bosu squats, single leg squats, bridging with gymball and step ups. Then the evaluation is carried out by measuring the degree of pain using NRS, measuring muscle strength with MMT, and also measuring Range of Motion using a Goniometer. Conclusion: Rehabilitation program after ACL reconstruction using balance and strengthening exercises including: SEBT (Star Excursion Balance Test), dynamic bosu squats, single leg squats, bridging with gymball and step ups can improve balance, increase muscle strength, and improve the functional abilities of patients after ACL reconstruction.